2015
DOI: 10.1093/pm/pnv053
|View full text |Cite
|
Sign up to set email alerts
|

Intradiscal Platelet-Rich Plasma Injection for Chronic Discogenic Low Back Pain: Preliminary Results from a Prospective Trial

Abstract: This trial demonstrates encouraging preliminary 6 month findings, using strict categorical success criteria, for intradiscal PRP as a treatment for presumed discogenic low back pain. Randomized placebo controlled trials are needed to further evaluate the efficacy of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 70 publications
3
98
1
3
Order By: Relevance
“…Several studies have demonstrated improvement in clinical scores including ODI, VAS, and JOA beginning 1 month post-PRP injection [64][65][66][67]. Additionally, these studies have reported no complications associated with MSC and PRP injections [64].…”
Section: Treatment Non-operativementioning
confidence: 95%
“…Several studies have demonstrated improvement in clinical scores including ODI, VAS, and JOA beginning 1 month post-PRP injection [64][65][66][67]. Additionally, these studies have reported no complications associated with MSC and PRP injections [64].…”
Section: Treatment Non-operativementioning
confidence: 95%
“…Levi et al studied 22 patients who underwent intradiscal PRP injection with a 6-month follow-up. Categorical success rate rose from 14% at 1 month, 32% at 2 months, to 47% at 6 months of at least 50% improvement 78. A prospective, double-blinded, randomized, placebo controlled study of 47 patients showed significant improvement outcomes in the intradiscal injected PRP group with regard to pain.…”
Section: Introductionmentioning
confidence: 94%
“…Optimization of indication (to distinguish responders and nonresponders), cell‐source, cell concentration, and scaffold type are needed, as are larger‐scale clinical trials to show long‐term safety and efficacy. Intradiscal PRP injection seems safe; however, its efficacy remains unclear . Chondrocyte transplantation studies showed some positive results in a small number of participants; further studies are needed to show efficacy .…”
Section: Available Clinical Treatments For Discogenic Painmentioning
confidence: 99%